The Main Place Of Linguo-Cultural Studies In World Linguistics And Its Development As A Science - D.U.Ismoilova (Zien Journals, 2024)
This article is devoted to the study of linguoculturology that is considered a modern science in linguistics. The article reveals the linguoculturological studies that were held by different linguists such as Maslova, Vorobyov, Telia and its emergence as a new science in linguistics. Moreover, there are examples of realia and lacunae which are indispensable part of linguoculturology.
Keywords: language; culture; linguists; linguoculturology